If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1y + -3 = 2x + 5 Reorder the terms: -3 + 1y = 2x + 5 Reorder the terms: -3 + 1y = 5 + 2x Solving -3 + 1y = 5 + 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 1y = 5 + 3 + 2x Combine like terms: -3 + 3 = 0 0 + 1y = 5 + 3 + 2x 1y = 5 + 3 + 2x Combine like terms: 5 + 3 = 8 1y = 8 + 2x Divide each side by '1'. y = 8 + 2x Simplifying y = 8 + 2x
| Logx=-5.9 | | 3(x+6)(x-2)=60 | | 3x^2-130x-3000=0 | | -1-m/10=1 | | 4/2=9/x | | 6x-7(-2x+5)=65 | | 3(x+60)(x-2)=60 | | -0.75n-21=-15 | | 9√25/√50 | | 5h^2-605=0 | | 13y+x=66 | | 4v/10 | | -3(x-4)=24 | | y=0x-6 | | 2m^2+80m=0 | | X+2=2.10 | | tan(40=3/x | | 7.5-2n=-2 | | 9-8x=-4-8x | | x-3/15x6x-18/5x | | -2a=10+(-7) | | cosx+sinx=2x | | x^2-48x=-104 | | 2(6x^2+11)=0 | | 7.68=3x | | ((400-2x)/2)x | | 9u^2-162u=0 | | 3x^2-6x+21=0 | | 12x^2=22 | | 88=r-92 | | -28=-4n-4 | | (400-2x/2)x |